Indian banking industry: a new evidence from a profitability perspective - Rai, Shailendra; Chabot, Miia; Bertrand, Jean-Louis; Shaikh, Imlak (Business: Theory and Practice, 2021)
While India is set to become the world’s most populous country by 2050, it is also the home to the world’s largest number of unbanked individuals. This paper aims to investigate the profitability issue with a focus on public banks. Using a new methodology based on comparisons tests and panel analysis that test unobserved heterogeneities between banks. We show that public banks are not low performers, nor can private banks be considered high performers Finally, we show that the proportion of non-performing assets (NPAs) is a real concern and requires urgent attention of government and regulators for Indian banks to serve profitability their home market. Banks that make more profits on non-interest income are not necessarily less profitable than others. Further, outcomes favour the ideas that if public banks are able to clean-up their non-performing assets as well as follow a sound prudential regulation, their profits could strongly grow. Future reforms must consider the public bank’s key role in the growth of the India’s economic outlook, especially when it comes to projects of social importance and national priority. The study is based on 105 banks with cross-sections from 2003–2016; however, India’s government has initiated reforms in the banking segment, which has led to a significant decrease in government stake and the number of banks.